The attitudes of nurses towards HIV positive patients - Estelle Deetlefs; M Greeff; M P Koen (AOSIS, 2003)
AIDS is increasing in South Africa at an alarming rate. Registered nurses consequently have more frequent contact with HIV positive patients. Opsomming VIGS neem drasties toe in Suid-Afrika. Geregistreerde verpleegkundiges het gevolglik meer gereelde kontak met MIV-positiewe pasiënte. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.